Crank-Nicolson scheme for a logarithmic Schrödinger equation - Abidi , Mariem; Goubet, Olivier; Martin , Véronique (North-Western European Journal of Mathematics, 2022)
We discuss here a classical Crank-Nicolson numerical scheme to approximate the solutions of a nonlinear equation Schrödinger that reads\[u_t-i\partial_x\left( u(x)\partial_x u\right)-iu\log |u|^2=0.\]